Kurikulum Bimbingan dan Konseling di Sekolah Menengah Kejuruan dalam Upaya Menghadapi Tantangan Era Revolusi Industri 4.0 - Surur, Naharus; Makhmudah, Ulya; Dewantoro, Adi; Hartanto, Agit Purwo; Wulandari, Arifah; Fatmawati, Diah (Bulletin of Counseling and Psychotherapy, 2021)
This research is a follow-up research and development of a comprehensive guidance and counseling curriculum in SMK in the industrial revolution’s era 4.0. The existence of manufacturing technology that has entered the trend of automation and data exchange, including cyber-physical systems, namely the internet of things (IoT), cognitive computing and digitization in various aspects of life, makes vocational education a challenge in preparing human resources who are able to contribute active according to the area of ​​expertise for the progress of the nation in the industrial revolution’s era 4.0. The development of a guidance and counseling curriculum in SMK that is responsive to the era of the industrial revolution 4.0 includes the development of methods, strategies and service materials, namely in accordance with comprehensive, competency-based guidance and counseling. This curriculum will contain: the services and objectives of each domain, the formulation of class level competencies (measurable student success standards), details of activities that students and counselors must do in one unit of time. The development of this curriculum uses the research and development design of Borg and Gall which has reached the small group test stage. The small group test was carried out on 15 Vocational School Counseling Teachers throughout the Surakarta Ex-Karesidenan by selecting subjects using the random sampling method. The results of the small group test showed a indicator very good in the academic, career, and personal or social fields.